The Art, to Listen: a Musical Analysis of the Composition IN FRIENDSHIP - Stockhausen, Karlheinz 1928-2007; McGuire, John (Kürten Stockhausen-verlag, 2015)
Based on lectures given Oct. 25, 1980 at the University of Mainz and Nov. 17, 1982 at Koninklijk Conservatory at the Hague and expanded with additional commentary in 1989. This translation was made by John McGuire in 1999 and edited by Susanne Stephens in 2000.Musical examples are from the published score of "In friendship" for clarinet.
Keywords: Musical analysis